Clinical and genetic characteristics of hemoglobin H disease in Iran. (18th August 2022) - Abolghasemi, Hassan; Kamfar, Sharareh; Azarkeivan, Azita; Karimi, Mehran; Keikhaei, Bijan; Abolghasemi, Fahimeh; Radfar, Mohammad H.; Eshghi, Peyman; Alavi, Samin
Abstract: Hemoglobin H (Hb H) disease is a subtype of α-thalassemia caused by deletional and/or non-deletional mutations in three alpha-globin genes in which the various genotypes determine the disease severity. This study was aimed to investigate the frequency of alpha gene mutations and genotypes and their correlation with hematological and clinical characteristics in Iran. Among 202 patients diagnosed with Hb H disease through a national study in Iran according to standard methods, we had access to the hematologic and clinical findings and genetic data of 101 patients in whom genetic study was performed. Genomic DNA from peripheral blood was extracted and analyzed for identification of α-globin gene mutations using Multiplex Gap Polymerase Chain Reaction, Reverse Hybridization Assay, and finally Direct DNA Sequencing method. Twenty-one different mutations and thirty genotypes were detected in 101 patients with Hb H disease. In total, 39 patients (38.6%) were deletional and 62 patients (61.4%) were non-deletional type of the disease. The – MED mutation was highly prevalent in almost half of the patients (56.4%). Among various genotypes, – MED /-a 3.7 (29.7%) and -α 20 .5 /-α 5NT (6.9%) were the most prevalent genotypes found in the studied group. Patients with non-deletional type presented with more severe hematological and clinical findings. Hb H percentage and serum ferritin levels were significantly higher in non-deletional patients in comparison to the deletional group ( p < 0.05). 12 (11.9%) and 40 (39.6%) out of 101 patients were on regular and occasional transfusions, respectively. 83% of those with regular transfusion belonged to the non-deletional group. Among transfusion-dependent patients, – MED /α CS α and α 20 .5 /-α 5NT were the most common genotypes. In this study, two patients with -α 20 .5 /α CS α and – MED /α −5NT genotypes experienced thrombotic events. This study indicated that although non-deletional genotypes of Hb H disease were responsible for more clinical severity of the disease, due to the presence of severe phenotypes even in deletional types, no definite correlation was found between genotype and phenotype.